Genomic-based phylogenetic and metabolic analyses of the genus Natronomonas, and description of Natronomonas aquatica sp. nov. - García-Roldán, Alicia; Durán-Viseras, Ana; de la Haba, Rafael R.; Corral, Paulina; Sánchez-Porro, Cristina; Ventosa, Antonio (Frontiers in Microbiology, 2023)
The genus Natronomonas is classified on the family Haloarculaceae, within the class Halobacteria and currently includes six species isolated from salterns, saline or soda lakes, and salt mines. All are extremely halophilic (optimal growth at 20-25% [w/v] NaCl) and neutrophilic, except Natronomonas pharaonis, the type species of the genus, that is haloalkaliphilic (showing optimal growth at pH 9.0) and possesses distinct phenotypic features, such as a different polar lipid profile than the rest of species of the genus. We have carried out a genome-based study in order to determine the phylogenetic structure of the genus Natronomonas and elucidate its current taxonomic status. Overall genomic relatedness indexes, i.e. OrthoANI (Average Nucleotide Identity), dDDH (digital DNA–DNA hybridization) and AAI (Amino Acid Identity), were determined with respect to the species of Natronomonas and other representative taxa of the class Halobacteria. Our data show that the six species of Natronomonas constitute a coherent cluster at the genus level. Besides, we have characterized a new haloarchaeon, strain F2-12T, isolated from the brine of a pond of a saltern in Isla Cristina, Huelva, Spain, and we determined that it constitutes a new species of Natronomonas, for which we propose the name Natronomonas aquatica sp. nov. Besides, the metabolic analysis revealed a heterotrophic lifestyle and a versatile nitrogen metabolism for members of this genus. Finally, metagenomic fragment recruitments from a subset of hypersaline habitats, indicated that the species of Natronomonas are widely distributed in saline lakes and salterns as well as on saline soils. Species of this haloarchaeal genus can be considered as ubiquitous in intermediate to high saline habitats.